Investigating the Effects of Problem Based Learning on Students’ Vocabulary Mastery - Agrissto Bintang Aji Pradana (Institut Agama Islam Negeri Palopo, 2022)
Vocabulary mastery has crucial roles in language learning. Learners would be unable to engage in language development activities such as grammar, reading, and writing if they did not have adequate vocabulary. This study aimed to determine the effects of Problem Based Learning model on vocabulary mastery. It involved 18 grade students living in Windusari Village, Magelang. Due to interaction restriction on Pandemic era, it was not conducted at school. Pre-Experimental Designs was employed in this study. There was one group as the sample given 4-meeting-treatment. The data were gathered through tests consisting multiple choice items assumed to be valid through Product Moment Test. Then they were statistically analyzed using Paired Sample t-test. The result revealed that Asymp Sig (2-tailed) was 0.000 and the t value was 14.806 > t table 2.10982. In sum, there was a positive and significant influence of Problem Based Learning to increase the vocabulary mastery.